Evolution of international environmental regimes : the case of climate change - Schiele, Simone (Cambridge, UK : Cambridge University Press, 2014)
'Drawing specifically on the international climate regime, Simone Schiele examines international environmental regimes from a legal perspective and analyses a core feature of international regimes - their ability to evolve over time. In particular, she develops a theoretical framework based on general international law which allows for a thorough examination of the understanding of international law and the options for law-creation in international environmental regimes. The analysis therefore provides both a coherent understanding of the international climate regime and a starting point for further research in other regimes'--
Machine generated contents note: 1. Introductory observations and approach; 2. International environmental regimes and their treaties; 3. International climate regime; 4. Effectiveness of international environmental regimes and'creative legal engineering'; 5. International regimes as normative systems; 6. Methodology for determining the norms, sources and underlying theories of international law in the international climate regime; 7. Sources of legal norms in the international climate regime and the negotiations leading up to and at the Copenhagen conference; 8. Sources of legal norms in the international climate regime and Compliance Committee methods of interpretation; 9. Increasing robustness of the international climate regime as a system of norms; 10. Conclusions.
Includes bibliographical references and index.
Keywords: Environmental policy -- International cooperation; Environmental protection -- International cooperation; Environmental law, International